Fuel cell - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Chin, Mei Lee; Siti Aisah, Harun; Norhayati, Nordin; Ezrinda, Mohd Zahidee; Mohd Fazli, Farida Asras; Nurul Nadia, Abd Razak (Penerbit UMP, 2011)
With the current debates over energy, more people are aware of the benefits and potential applications of fuel cells. The principle of the fuel cell was discovered by German scientist Christian Friedrich Schonbein in 1B3B. Fuel cells produce energy without combustion by an electrochemical process using hydrogen fuel. A fuel cell consists oftwo electrodes sandwiched around an electrolyte. Oxygen (from the air) enters the fuel cell through the cathode . Encouraged by a catalyst, the hydrogen atom splits into a proton and an electron, which take different paths to the cathode. The proton passes through the electrolyte. The electrons create a separate current that can be utilized before they are reunited wfth the hydrogen and oxygen to form water molecules.